2014
DOI: 10.1002/ijc.29098
|View full text |Cite
|
Sign up to set email alerts
|

Plasma insulin, C‐peptide and blood glucose and the risk of gastric cancer: The Japan Public Health Center‐based prospective study

Abstract: To date, the association between diabetes mellitus (DM) and gastric cancer has been controversial, including the underlying mechanism. We investigated the association between plasma diabetic biomarkers (insulin, C-peptide, and blood glucose) and gastric cancer risk. In addition, homeostasis model assessment of insulin resistance (HOMA-IR) and homeostasis model assessment of b-cell function (HOMA-b) were calculated. A total of 36,745 subjects aged 40-69 years in the Japan Public Health Center-based prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 41 publications
0
39
1
Order By: Relevance
“…Hyperinsulinemia and/or hyperglycemia because of insulin resistance (IR) are important components to the biological mechanisms underlying the association between diabetes and cancer . However, the results of prospective studies conducted in Korea and Japan remained heterogeneous despite the measurement of diabetic biomarkers such as serum insulin, glucose, C‐peptide, and hemoglobin A1c (HbA1c) …”
Section: Introductionmentioning
confidence: 99%
“…Hyperinsulinemia and/or hyperglycemia because of insulin resistance (IR) are important components to the biological mechanisms underlying the association between diabetes and cancer . However, the results of prospective studies conducted in Korea and Japan remained heterogeneous despite the measurement of diabetic biomarkers such as serum insulin, glucose, C‐peptide, and hemoglobin A1c (HbA1c) …”
Section: Introductionmentioning
confidence: 99%
“…Hyperinsulinemia is the most prominent feature of type 2 diabetes, as a result of insulin resistance. The high level of insulin is a risk of gastric cancer for promotion of cell proliferation[3]. This possibility is supported by a study in mice, in which hyperinsulinemia promoted gastric tumor growth in diet-induced obesity[25].…”
Section: Discussionmentioning
confidence: 99%
“…However, hyperinsulinemia and insulin-like growth factor (IGF) may play a central role in the promotion of tumorigenesis. A large Japanese case-control study has demonstrated that hyperinsulinemia and serum C peptide are positively correlated with increased risk of gastric cancer[3]. A high level of insulin increases the bioavailability of serum IGF-1.…”
Section: Introductionmentioning
confidence: 99%
“…In the e-heathcare cloud example, some decision making model can be used to automatically check a patients' health status. The parameters of the decision making model frequently contain real numbers (e.g., the probability used in the naïve Bayes model [8]), so do the outsourced personal health data (e. g., blood glucose, insulin, and C-peptide levels are often constructed as non-integer, see the recent study involving 36,745 subjects aged 4069 years in the Japan Public Health Center-based prospective study [9]). However, cryptosystems are generally designed to protect only integer values and computations on integers affect the accuracy of data and decision making results, and even may lead to wrong diagnosis of a patient's illness.…”
Section: Introductionmentioning
confidence: 99%
“…Step-3 can be parallel executed which only takes one round communication 9. Note that x · y = x × y (defined in Section V-A).…”
mentioning
confidence: 99%